Shinto (the Way of the Gods) - Aston, W. G. (William George), 1841-1911 (Salt Lake City, UT : Project Gutenberg, 2014)
"Shinto (the Way of the Gods)" by W. G. Aston is a historical account written in the early 20th century. The book serves as an exploration of Shinto, the ancient religion of Japan, detailing its practices, beliefs, and development over time. It delves into aspects such as the pantheon of deities, the concept of kami, and the cultural and historical influences shaping Shinto literature. At the start of the work, Aston lays the groundwork for exploring Shinto by addressing its foundational elements and historical context. He discusses its rudimentary aspects compared to other world religions, touching on its polytheism and lack of a supreme deity. The opening also highlights how Shinto evolved from a primitive cult into a more organized religion, emphasizing its strong ties to Japanese culture and civilization. Additionally, Aston introduces various sources for studying Shinto, including ancient texts like the "Kojiki" and "Nihongi," which provide insight into its mythology and rituals. (This is an automatically generated summary.)
Release date is 2014-06-21
E-text prepared by Delphine Lettau, Paul Marshall, Mary Akers, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/Canadian Libraries (https://archive.org/details/toronto)
Keywords: Shinto